Effects of Yersinia enterocolitica O:3 derivatives on B lymphocyte activation in vivo - Crespo, Adriana de Moraes Costa [UNESP]; Falcão, Deise Pasetto [UNESP]; Araújo, Paulo Maria Ferreira de [UNESP]; Medeiros, Beatriz Maria Machado de [UNESP] (Center Academic Publ Japan, 2002)
The potential sequelae of intestinal infection with Yersinia enterocolitica include reactive arthritis, erythema nodosum, Reiter's syndrome and other autoimmune diseases. The role of the immune response in the pathogenesis of these diseases has not been fully defined, but autoimmune manifestations may be a consequence of the increase in autoantibodies as a result of polyclonal B-cell activation induced by Yersinia. We investigated the effects of Y enterocolitica 0:3 derivatives on B lymphocyte activation in vivo. Groups of five specific pathogen free (SPF) Swiss mice were inoculated with bacterial cell extract, Yersinia outermembrane proteins (Yops) or lipopolysaccharide (LPS) obtained from Y enterocolitica 0:3 and their immunoglobulin-secreting spleen cells were detected by isotype-specific protein A plaque assay. The presence of specific anti-Yersinia antibodies and autoantibodies was determined in mouse sera by ELISA. In all experiments a marked increase in the number of secretory cells of different isotypes was observed as early as the third day after inoculation. IgG and IgM anti-Yersinia antibodies were detected in the sera of all inoculated mice, and autoantibodies against myosin in the sera of those inoculated with bacterial cell extract. The sera from animals stimulated with LPS reacted with myelin, actin and laminin, while the sera from mice inoculated with Yops reacted with myelin, thyroglobulin and cardiolipin. These results suggest that SPF Swiss mice inoculated with any one of the Y enterocolitica derivatives tested exhibited polyclonal activation of B lymphocytes as a result of stimulation by various bacterial components and not only LPS stimulation.
Keywords: LPS; Polyclonal activation; Yersinia enterocolitica; Yops; Actin; Autoantibody; Bacterium lipopolysaccharide; Cardiolipin; Immunoglobulin G antibody; Immunoglobulin M antibody; Laminin; Myelin; Myosin; Outer membrane protein; Thyroglobulin; Animal experiment; Antibody detection; Antibody specificity; Autoimmune disease; B lymphocyte activation; Controlled study; Enzyme linked immunosorbent assay; Erythema nodosum; Immunoglobulin production; Intestine infection; Mouse; Nonhuman; Reactive arthritis; Reiter syndrome; Spleen cell; Actins; Animals; Antibodies, Bacterial; Autoantibodies; B-Lymphocytes; Bacterial Outer Membrane Proteins; Immunoglobulin G; Immunoglobulin M; Lipopolysaccharides; Lymphocyte Activation; Mice; Myelin Sheath; Myosins; Specific Pathogen-Free Organisms; Spleen; Yersinia Infections; Animalia; Bacteria (microorganisms); Negibacteria; Yersinia